Historic review about the life and contribution of Doctor Javier Arias-Stela - Takano-Morón, Juan (2020)
Dr. Javier Arias-Stella distinguished peruvian pathologist is knowed in the field because achievement of his discovery which has his name: “Arias-Stella-Reaction”. This discovery which was started at Pathology Institute ahead by Profesor Pedro Weiss Harvey in San Marcos University, was the beginning along his life which is giving in his contribution of knowledge of gynecologic pathology, pulmonary-cardiovascular anatomy and pathology of people living at high altitude at the Peruvian Andes mountain- and other topics of pathology. In tandem of is research advanced, his teacher activities taking place at UNMSM and UPCH which can be expressed thought his disciples who practice medicine at hospitals in Peru and other countries. Dr. Arias-Stella also had active participation in politic life of Perú.